STRATEGI MASA DEPAN DENGAN SEMANGAT KEWIRAUSAHAAN - Ahmadireja, Ahmadireja (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2015)
In carrying out entrepreneurial importance of the master plan for mental shape the creative and innovative early. All levels and education levels also have to accept entrepreneurial learning entrepreneurship education and training. Because entrepreneurship is about independence. Entrepreneurship can be defined as soul, spirit, attitude, behavior, and the potential of a person's ability to handle a business or activity that leads to the search for, create, implement ways of working, technologies, and new products to improve efficiency in order to provide better service. Competitiveness, innovation and economic growth depends on the ability to produce future leaders with the skills, attitudes and behaviors to become entrepreneurs and at the same time socially responsible. Entrepreneurship is not just about creating a business plan and business. It's also about creativity, innovation and growth, ways of thinking and acting that are relevant to all parts of the economy and society as well as the entire surrounding ecosystem. In developing entrepreneurship, graduates of higher education has an important role to play. This can be understood as a lifelong process that develop individual skills, attitudes and behaviors. It is important to start as early as possible at all levels of formal and informal education. It must be integrated into the education system of primary and secondary schools and higher education.